Integration of social networks and recommendation of social activities (III) - Long, Xiat Fei. (2011)
This project was done under the supervision of Assistant Prof Zhang Jie. This project is to develop a web-based intelligent interface to integrate several social networks together. The interface is also capable of providing personalized recommendations about which social activities of others should be shown to the users of the interface.